Acidic Exopolysaccharide Flocculant Produced by the Fungus Mucor rouxii using Beet-Molasses - Abdel-Aziz, Shadia M.; Hamed, Hoda A.; Mouafi, Foukia E. (Research in Biotechnology, 2012)
An acidicexopolysaccharide flocculant (EPF), produced by the fungus Mucor rouxii, was found to play an important role for protection of cells against abiotic stress such as extreme pH value. This EPF was produced during 48 hrs of growth, at 6% beet-molasses, pH 3.5 and 28oC. The chemical composition of beet-molasses includes heavy metals such as Zn2+, Cu2+, Fe2+, and Mn2+ which could be additional stress factors trigger the formation of the EPF. The fungus synthesized this EPF when exposed to low pH, as a form of self-protection. Different carbon sources induces the production of the EPF, however, beet molasses was the most effective and showed maximum production. Ammonium sulfate was theÃ‚Â preferred nitrogen source. Higher concentrations of beet molasses depressed fungal growth. The produced EPF exhibited flocculating properties; it possesses good flocculating activity for aggregation andÃ‚Â precipitation of charcoal particles where the flocculating activity reached approximately 99%. In addition, it showed maximum flocculating activity at acidic pH values and at high temperature. The main backbone of this EPF is a polysaccharide. Thus, by exploiting beet- molasses as inexpensive carbon source under acidic pH-shock, the fungus produced an EPF characterized by good flocculating properties. It could be utilized in the area of waste-water treatment, in drink water processing as well as in industrial fields.